Novel Single Nucleotide Polymorphisms in the Sumba Ongole (Bos indicus) Growth Hormone Gene - PASKAH PARTOGI AGUNG; WIDYA PINTAKA BAYU PUTRA; SAIFUL ANWAR; ARI SULISTYO WULANDARI; SYAHRUDDIN SAID; MOCH SYAMSUL ARIFIN ZEIN; ADITYA SUDIRO (Society for Indonesian Biodiversity, 2018)
Agung PP, Putra WPB, Anwar S, Wulandari AS, Zein MSA, Said S, Sudiro A. 2018. Novel Single Nucleotide Polymorphisms in the Sumba Ongole  (Bos indicus) Growth Hormone Gene. Biodiversitas 19: 676-681. The Sumba Ongole cattle  (Bos indicus) is one of the local Indonesian cattle breeds and has excellent potential to gain higher carcass yield compared to other local cattle breeds in Indonesia. The Growth Hormone  (GH) gene was a potential target for molecular study due to its importance as growth regulating hormone. This study was aimed to determine Single Nucleotide Polymorphism  (SNP) profile of the GH gene in the Sumba Ongole  (SO) cattle using PCR and DNA sequencing methods from 34 individual DNA samples. The results from this study showed that there are 28 SNPs identified within the GH gene; Twenty one SNPs were found to occur in the intron region, 4 SNPs in the exon region, and 3 SNPs in the 3’ end region. There were 17 SNPs in the SO cattle GH gene were caused by novel mutation. The novel SNP g.1395insC was found only in the SO cattle. Moreover, the frequency of the SNP g.1395insC was the highest among other novel SNPs in the SO cattle GH gene. The moderate PIC value  (0.25<PIC<0.50) were found in two novel SNPs i.e. SNP g.1415C>G  (intron 4), and SNP g.1526A>G  (intron 4). The GH gene in the SO cattle was polymorphic and the 17 novel SNPs need to be further validated.